One of the methods is:
elimination of x, then elimination of y,
solve z, find y en find x. (It may be another order.)
Elimination of X
X = 6 - Y and X = -2 - Z
So 6 - Y = -2 - Z
Now we have
6 - Y = -2 - Z or Y = Z + 8 and Y+Z=2
Elimination of Y gives (Z + 8) + Z = 2
Solve Z
2Z = -6 or Z = -3
Find Y
Y = Z + 8 = -3 + 8 = 5
Find X
X+Y=6. So X + 5 =6 and X=1
Conclusion: (X,Y,Z) = (1 , 5 , -3)
The check you can do yourself.
2006-07-20 10:22:10
·
answer #1
·
answered by Thermo 6
·
6⤊
1⤋
U can find the value by using Matrices & detrminants
By using Cramar's law (determinants):
system of equation must have the 3 variables in each equation
(if there is a variable doesn't exist in an equation, we put it & multiply it by zero)
therfore the system of equation:
X + Y + (0*Z) = 6
X + Z + (0*Y) = -2
Y + Z + (0*X) = 2
then apply Cramar's law of determinants
i hope u got ur point from my explanation
2006-07-20 08:16:36
·
answer #2
·
answered by Kevin 5
·
0⤊
0⤋
For your example, Let the above equations equal "1", "2", and "3", as follows:
1. X+Y = 6
2. X+Z = -2
3. Y+Z = 2
Add equation 1 to equation 2 and subtract by equation 3. You now have 2X = 2, so X = 1. From this, you can find ouy that Z=-3, and Y=5.
2006-07-20 08:02:05
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Two equations at a time:
X+Z=-2
Y+Z=2
Z = -2 - X
Y + (-2 - X) = 2
Y - X = 4
Use this result with the other given equation:
Y - X = 4
X + Y = 6
Add them together:
2Y - X + X = 10
2Y = 10
Y = 5
X + (5)=6, X = 1
(1) + Z=-2, Z = -3
2006-07-20 16:22:41
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
you have 3 variables, and 3 equations. Try expressing 'x' in terms of " y and z" or 'y' in terms of 'x and z' or 'z' in terms of 'x and y'.
For example:
since equation 1 is:
x + y = 6, therefore x = 6 - y.
equation 2 can now be written as: (6 - y)+ Z= -2
which is: - y+z = -2-6 = -8
hence equation 2 is now : z-y = -8
equation 3 is already in terms of 'y and z'.
z + y = 2
z - y = -8
you can now solve them simultaneously.
2006-07-20 08:38:52
·
answer #5
·
answered by human 1
·
0⤊
0⤋
first solve x in equation1 ( x=6-y ), substitute that in for x of eq2 ( 6-y+z=-2 ) and solve for y ( y=8+z ), sub that into eq3 ( 8+z+z=2 ) and solve for z ( z=-3 ) sub back into the other eqs for z=-3, y=5, and x=1.
2006-07-20 08:52:53
·
answer #6
·
answered by bigdog2all2 1
·
0⤊
0⤋
3x-2y+z=-4 ----------------- (a million) 5x+2y-2z=-9 ----------------- (2) -2x+y+3z = 20 ----------------- (3) upload equation (a million) with (2): (this might cancel the y variable) 3x+5x+z-2z = -4- 9 8x-z = -13 z = 8x+13 ---------- (4) replace (4) in (3): -2x+y+3(8x+13) = 20 -2x+y+24x+39 = 20 y+22x = -19 y = -22x-19 ---------- (5) replace (4) and (5) in (a million): 3x-2(-22x-19)+8x+13 = -4 3x+44x+38+8x+13 = -4 55x = -fifty 5 x = -a million we've x = -a million, hence y = 3 and z = 5 (via substituting x = -a million in (4) and (5))
2016-11-02 10:17:20
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
also solve and sub works
Solve 3. for Z
Z=2-Y
Substitute Z into 2.
X+2-Y=-2
and solve for X
X=-4+Y
Sub X into 1.
-4+Y+Y=6
2Y=10
Y=5
Find X
X=1
Find Z
Z=-3
Some systems work better with different methods
2006-07-20 08:08:20
·
answer #8
·
answered by Jake S 5
·
0⤊
0⤋
u should try to figyre it u r self
its a simple thing looking at last equation which is terms of y n z make another eqn in trms of y n z from 1 & 2
and then solve it
2006-07-20 08:20:25
·
answer #9
·
answered by rony 1
·
0⤊
0⤋
make a triangle matrix of it
:..aX + bY + cZ = d
:..........eY + fZ = g
:..................hZ = i
next solve Z = i/h;
then Y, then X
1X + 1Y +0Z = 6
........1Y + 1Z = 2
1X + 0Y +1Z = -2
subtract from last row the first row :
1X + 1Y +0Z = 6
........1Y + 1Z = 2
........-Y +1Z = -8
add second row to last row
1X + 1Y +0Z = 6
........1Y + 1Z = 2
........ +2Z = -6
now solve Z = -6/2, then Y = 2 - Z = 2+3 = 5 etc etc
2006-07-20 08:07:08
·
answer #10
·
answered by gjmb1960 7
·
0⤊
0⤋